Fundamental of Entrepreneurship ENT300 : Tempe Pak Gun / Fatin Farhána Mohamad Yusuf ... [et al.] - Mohamad Yusuf, Fatin Farhána; Malek, Fatin Athirah; Francis, Jonah; Rickino, Mohd Haziq Zikri; Sahari, Mohd Arrabe; Ahmad Aziz, Asyraf (2016)
Tempe Pak Gun is the sole proprietorship business by Puan Noraini Binf Salleh, at first she concentrated her selling goods on Tempeh, a traditional soy product originating from Indonesia and may expand her business whenever there are capability and chances is presented The owner of Tempe Pak Gun, Puan Noraini Binf Salleh is a very hardworking entrepreneur, who hates to give up and dare to. take risk for success. The busmess began on 2011 and have help supported her family until now.It was the idea of her husband to sell Tempeh at Oya, being that Oya is an untapped market when it comes to selling Tempeh. Taking the initiative, Puan Noraini Salleh quits her job and began working on her own. It was hard at first but now, Tempe Pak Gun has become a successful business in Oya, where she become the main supplier of Tempeh. It is no secret that one of her reason of success is there is no direct competition in Oya to them.